2019
DOI: 10.1371/journal.pone.0218892
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, culturing and gene expression profiling of inner mass cells from stable and vulnerable carotid atherosclerotic plaques

Abstract: The connective tissue components that form the atherosclerotic plaque body are produced by the plaque inner mass cells (PIMC), located inside the plaque. We report an approach to isolate and culture cells from the connective tissue of stable and vulnerable human atherosclerotic plaques based on elimination of non-connective tissue cells such as blood and non-plaque intima cells with a lysis buffer. The resulting plaque cells were characterized by growth capacity, morphology, transcriptome profiling and specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…We tested two culture media - IMDM-FBS (14) and HAM F12K Complete (designed in-house, see Methods), in combination with Matrigel, Vitronectin, and Fibronectin pre-coated plates, and in the presence and absence of Vitamin C. Figure 1 provides an overview of the methodology of the conditioned outgrowth method, which is based on the capability of plaque cells to migrate from 2-3 mm 2 plaque pieces (Fig. S1 A) and proliferate in the dish.…”
Section: Resultsmentioning
confidence: 99%
“…We tested two culture media - IMDM-FBS (14) and HAM F12K Complete (designed in-house, see Methods), in combination with Matrigel, Vitronectin, and Fibronectin pre-coated plates, and in the presence and absence of Vitamin C. Figure 1 provides an overview of the methodology of the conditioned outgrowth method, which is based on the capability of plaque cells to migrate from 2-3 mm 2 plaque pieces (Fig. S1 A) and proliferate in the dish.…”
Section: Resultsmentioning
confidence: 99%
“…MAIT T cells are unconventional T cells with innate‐like antimicrobial activity but have also been assigned various deleterious and protective functions in autoimmune, inflammatory, and metabolic diseases 78 and might thus play a role in the atherogenic vasculature. Cpne7 has not been investigated in the context of atherosclerosis, but the inner mass cells from vulnerable carotid atherosclerotic plaques express higher Cpne7 levels than the ones from stable plaques, inferring that Cpne7 might have a role in the progression of atherosclerosis 79 …”
Section: Discussionmentioning
confidence: 99%
“…Cpne7 has not been investigated in the context of atherosclerosis, but the inner mass cells from vulnerable carotid atherosclerotic plaques express higher Cpne7 levels than the ones from stable plaques, inferring that Cpne7 might have a role in the progression of atherosclerosis. 79 We did not observe changes in BCA plaque VSMC numbers, but notably, Col4a1 and Tnnt3 (as well as Tnnt2), were among the top-enriched genes in our transcriptomic analysis, indicating effects on VSMC phenotype. Col4a1 was highly enriched in the 24-week Mif-deficient mice as well as in the 42-week paradigm, when comparing Mif-expressing to Mif-deficient mice.…”
Section: Discussionmentioning
confidence: 99%
“…In searching for the source of the microparticles expressing CD105 during the development of atherosclerosis, multiple research groups have identified cells with an unstable, vulnerable atherosclerotic plaque expressing CD105 [ 87 , 88 , 89 ]. During the development of atherosclerotic plaques, it was found that vasculature invades into the plaques.…”
Section: Prediabetes-facilitated Extracellular Vesicles Release In Atherosclerosismentioning
confidence: 99%